Professional learning competences and tasks in primary English teacher education curricula in Portugal - Vieira, Flávia (2024)
UIDB/04097/2020 UIDP/04097/2020 https://doi.org/10.54499/UIDB/04097/2020 https://doi.org/10.54499/UIDP/04097/2020